Formation of the professional subject of future psychological and pedagogical specialists in higher education - Stryzhakov, Artem; Khrolenko, Maryna; Matsenko, Lesya; Koycheva, Tetyana; Moiseienko, Natalia (Amazonia Investiga, 2023)
The article substantiates the peculiarities of the formation of professional subjectivity of future specialists in the field of psychology and pedagogy in the environment of higher education. The essence of the concepts "subjectivity", "subject", "professional subjectivity of a specialist" is revealed. The stages of the development of students' subjectivity in the process of professional training are distinguished: the objective-subjective stage of development; the objective stage of development; the subjective-objective stage of development and the actual subjective stage of development. The main functions of the student as a subject of activity are considered. When considering the possibilities of development of the individual's subjectivity, the mechanisms that determine the direction and dynamics of the progress of the personal and professional formation of the individual and its development are grouped. It is proved that the student's subjectivity manifests itself in the process of activating the following mechanisms: self-actualization, self-development, self-presentation, self-realization, and self-determination. In the radius of the educational environment of the higher school, attention is paid to the conditions, and the possibilities of realization of the internal possibilities of the formation of subjectivity are determined.